mdm2 expression is induced by wild type p53 activity. - Barak, Y (1993)
We have recently characterized a 95 kDa protein, p95, which exhibits enhanced binding to temperature-sensitive p53 (ts-p53) when cells are shifted down to 32.5 degrees C, a temperature at which ts-p53 possesses wild-type (wt)-like activities. In the present study we show that p95 is a product of the mdm2 putative proto-oncogene. The enhanced complex formation of mdm2 with ts-p53 in cells maintained at 32.5 degrees C is due to an elevation in total mdm2 protein levels following the temperature shift. We further demonstrate that the induction of mdm2 expression by t p53 activity is at the mRNA level. The induction occurs with very rapid kinetics and does not require de novo protein synthesis, suggesting a direct involvement of p53 in the process. Based on these data and on recent findings implicating p53 as a transcription factor, we suggest that the mdm2 gene is a target for activation by wt p53. In view of the ability of mdm2 to act as a specific antagonist of p53 activity, this induction process may serve to tightly autoregulate p53 activity in living cells.